First fossil frog from Antarctica: Implications for Eocene high latitude climate conditions and Gondwanan cosmopolitanism of Australobatrachia - Mörs, Thomas; Reguero, Marcelo Alfredo; Vasilyan, Davit (Scientific Reports)
Cenozoic ectothermic continental tetrapods (amphibians and reptiles) have not been documented previously from Antarctica, in contrast to all other continents. Here we report a fossil ilium and an ornamented skull bone that can be attributed to the Recent, South American, anuran family Calyptocephalellidae or helmeted frogs, representing the first modern amphibian found in Antarctica. The two bone fragments were recovered in Eocene, approximately 40 million years old, sediments on Seymour Island, Antarctic Peninsula. The record of hyperossified calyptocephalellid frogs outside South America supports Gondwanan cosmopolitanism of the anuran clade Australobatrachia. Our results demonstrate that Eocene freshwater ecosystems in Antarctica provided habitats favourable for ectothermic vertebrates (with mean annual precipitation ≥900 mm, coldest month mean temperature ≥3.75 °C, and warmest month mean temperature ≥13.79 °C), at a time when there were at least ephemeral ice sheets existing on the highlands within the interior of the continent. Fil: Mörs, Thomas. Stockholms Universitet; Suecia Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Vasilyan, Davit. University of Fribourg; Suiza